Can bivalve selective feeding shape phytoplankton community structure in the Ria Formosa coastal lagoon? - Coscollá, María Nohales (2024)
Phytoplankton plays a vital role in aquatic ecosystems, driving primary production, carbon cycling and nutrient recycling. The impact of bivalve feeding on phytoplankton biomass and community composition has been extensively documented. Nevertheless, there is currently no published research examining the impact of bivalve grazing and its selectivity on natural phytoplankton assemblages within the Ria Formosa coastal lagoon, a region responsible for 90% of Portugal's bivalve mollusc production. The aim of this study is to evaluate the impact of grazing by Mytilus galloprovincialis on natural phytoplankton assemblages in Ria Formosa. In particular, the effects of grazing on phytoplankton biomass, abundance, community composition, and the mussel's selectivity for different phytoplankton functional groups. The abundance and composition of phytoplankton were assessed using chlorophyll a concentration and microscopy: epifluorescence for pico- and nanophytoplankton and inverted for microphytoplankton. Mussel feeding was assessed by clearance rate. The microcosm experiments revealed a significant reduction in phytoplankton abundance due to mussel grazing in March, with a consistent decline in diatom abundance across all experiments. However, no significant changes were observed in phytoplankton biomass or community structure. The estimated per capita clearance rates of M. galloprovincialis ranged from 0.82 to 4.36 L h -1 individual-1 based on total chlorophyll a concentration, 1.07 to 1.95 L h -1 individual-1 based on total phytoplankton abundance, and 0.41 to 23.63 L h -1 individual-1 1 for specific phytoplankton groups. The results indicate that mussels selectively graze diatoms without significantly affecting overall phytoplankton biomass or community composition in Ria Formosa. Given the region's ecological and economic importance, understanding bivalve selective grazing is crucial for effective ecosystem management. Further studies should investigate the long-term impacts of this grazing on phytoplankton diversity and ecosystem resilience, particularly in light of changing conditions and growing aquaculture demands.